2019
DOI: 10.3892/mmr.2019.10633
|View full text |Cite
|
Sign up to set email alerts
|

BNIPL‑2 expression is correlated with the prognosis and regulates the proliferation of colorectal cancer through CD44

Abstract: Colorectal cancer (CRC) currently leads to many deaths worldwide. The regulatory mechanism, however, remains largely unclear. In the present study, bioinformatics methods were used to identify genes associated with CRC prognosis and to detect the molecular signals regulating the cell cycle in two CRC cell lines. It was revealed that BNIPL-2 expression was higher in CRC tissues than in adjacent tissue samples. Upregulation of BNIPL-2 was correlated with poor prognosis and the adverse malignant stages T and M. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…This significantly reduced cell proliferation in both cell lines (Figure 5 C) but impacted differently in terms of invasion, potentiating 5637 and decreasing the number of T24 invasive cells (Figure 5 D). These are novel findings linking CD44 to cell proliferation in BC, supporting previous observations for breast 63 and colorectal 64 cancers, and suggesting that intense splicing of extracellular domains may play a key role in driving invasion, in agreement with observations from patient samples. Since the percentage of CD44s is significantly higher in CD44-dependent invasive cells (75% in T24 vs 5% in 5637; Figure 3 D and S4) and significantly associated with invasion (Figure 1 A-B), we also concluded that this isoform maybe used to specifically target more aggressive cancer cells subpopulations.…”
Section: Methodssupporting
confidence: 90%
“…This significantly reduced cell proliferation in both cell lines (Figure 5 C) but impacted differently in terms of invasion, potentiating 5637 and decreasing the number of T24 invasive cells (Figure 5 D). These are novel findings linking CD44 to cell proliferation in BC, supporting previous observations for breast 63 and colorectal 64 cancers, and suggesting that intense splicing of extracellular domains may play a key role in driving invasion, in agreement with observations from patient samples. Since the percentage of CD44s is significantly higher in CD44-dependent invasive cells (75% in T24 vs 5% in 5637; Figure 3 D and S4) and significantly associated with invasion (Figure 1 A-B), we also concluded that this isoform maybe used to specifically target more aggressive cancer cells subpopulations.…”
Section: Methodssupporting
confidence: 90%
“…Poor prognosis induced by ERBB2 can alter the BNIPL expression, causing an anti-apoptotic phenotype [ 33 ]. In addition, overexpression of CD44 restores the cell proliferation suppressed by BNIPL‑2 and BNIPL-2, which can promote migration, invasion, and metastasis of colorectal cancer cells via CD44 [ 34 ]. In our research, overexpression of BNIPL inhibited the proliferation, migration, and invasion of LC cells.…”
Section: Discussionmentioning
confidence: 99%